Systematic Snooker Skills Test to Analyze Player Performance - Iwan Griffiths (International Journal of Sports Science and Coaching, 2014)
The process of rigorous training and coaching is one that is essential to any sports player aiming to develop their abilities further. From the novice player through to professional athletes, it is vital to maintain and assess their level of performance in order to progress to a higher standard. However, traditional practice routines can often be non-strategic and devised with an “ad-hoc” approach. In order for a training regime to be beneficial to a player, methods to examine a player's performance are desirable and can offer quantifiable feedback that will help the player to understand their current weaknesses and provide a benchmark to improve upon. This article focuses on the introduction of a systematic skills test. We assess the fundamental physics of snooker and from this we identify a set of key skills that characterises the basis of all snooker shots. We present 5 snooker tests that can be used to quantify the performance of these key skills. This allows us to analyse snooker players in an objective manner based on their level of ability for each key skill. The article concludes with a user study that assesses the performance of novice, intermediate and professional players when performing our proposed snooker skills test, which demonstrates the ability to make accurate comparison between players of different ability.